RAFT agent symmetry and the effects on photo-growth behavior in living polymer networks. Issue 35 (9th August 2021) - Bainbridge, Chris William Anderson; Broderick, Neil; Jin, Jianyong
Abstract : Here we describe how different symmetries of RAFT agent act after growth. Asymmetric networks showed a pore-filling behaviour, while symmetric networks underwent mesh-expansion. Abstract : In this work we present a study into the importance of RAFT agent symmetry for photo growth applications based on the one-pot photoexpandable/transformable-polymer networks (PET-PNs) RAFT network. For this we selected an asymmetrical RAFT agent 2-(butylthiocarbonothioylthio) propanoic acid (BTPA) and a symmetrical RAFT agent S, S -dibenzyl trithiocarbonate (DBTTC) to represent these two categories. We prepared 54 parent RAFT network gels. These covered three parameters, including RAFT agent symmetry, monomer to RAFT agent ratio ( i.e. RAFT concentration), and crosslinking degree. Subsequently, all of these gels would be grown to give 54 corresponding daughter gels. Additionally, 9 polymer networks based on conventional radical polymerization (FRP) were prepared as controls. In total, 117 polymer networks were studied and compared. We saw the asymmetric RAFT networks undergo a deswelling trend arising from their mesh-filling growth pattern. On the other hand, the symmetric RAFT networks demonstrated a mesh-expansion process, causing them to increase in swelling ratio. These results show the impact of changing a variable as small as the RAFT agent symmetry.